Subsistence entrepreneurships: concept, scopes and limits under the neoliberal model - Segura Gutiérrez, José Miguel; Vásquez Ávila, Lina Paola; Niño Gil, Jarrison; Segura Gutiérrez, José Miguel; Vásquez Ávila, Lina Paola; Niño Gil, Jarrison; Segura Gutiérrez, José Miguel; Vásquez Ávila, Lina Paola; Niño Gil, Jarrison (Corporación Universitaria Americana, 2020)
This article considers that in the subsistence entrepreneurships exist a social background, political and economic, which affects negatively the possibility of living worthily in the actual time and enjoy the freedom of participation that the marketing system offers. From there, it didn’t pretend to offer an unidirectional posture around such initiatives, but conversely, favor from a reflection supported by different authors, the identification of different ways of sociability, moral virtues and develop of capabilities in the subjects that require them, on the understood that these constitute themselves in alternative ways to affront the social crisis product of the early predation for the neoliberal economical directive, in those already impoverished contexts and with a strong threat in front of the possibility of living.